On Feynman’s paradox - Torres del Castillo, Gerardo Francisco (Revista Mexicana de Física E, 2023)
We review the Feynman paradox related to the conservation of the angular momentum in systems with an electromagnetic field. We show that the angular momentum is conserved if it is adequately defined.